Optimal Control Analysis of the Ebola Transmission Model with Vaccination - Siti Laelatul Chasanah; Dina Eka Nurvazly; Nufus Aulia (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Ebola virus disease (EVD) is a deadly disease caused by viruses within the genus Ebolavirus. Over 34,710 people have died from the virus globally, and outbreaks have shown that it spreads rapidly and uncontrollably. This research aims to find the optimal control to prevent the spread of EVD through vaccines. The population is divided into six, namely susceptible (), vaccinated (), infectious (), treated (), recovered (), and deceased (). We construct the model's optimal control parameters using the Pontryagin Principle. Vaccinations are only administered during specific periods. The optimal control interpretation was then obtained using numerical simulations. The results of this study indicate that the natural birth rate and the rate of contact of deceased humans have a much greater impact on the faster spread of the disease. Furthermore, it would be more effective to reduce the spread of EVD by providing vaccination compared to treating infected individuals. In conclusion, vaccination will be more effective if administered every two weeks. This is because it will lower the number of infected individuals significantly and reduce the cost of vaccination.